Gym Magazine. (Chicago : Victory Printing and Publishing Co., 1959)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : 179, West Washington Street, Chicago 2, III
Engels
Periodiek